Characteristics of Breast Cancer in Young Female Patients in Dr. Mohammad Hoesin General Hospital Palembang - Atik Diah Mutiara Ningsih; Nur Qodir; Ahmat Umar; Mulawan Umar; Puji Rizki Suryani; Citra Dewi (Indonesian Journal of Cancer, 2022)
Background: Breast cancer has had the highest mortality and morbidity globally in recent years. Breast cancer in young women presents with biological characteristics of more aggressive cancer, generally detected at advanced stage and a poorer prognosis. This study aimed to determine the characteristics of the incidence of breast cancer in young female patients at Dr. Mohammad Hoesin General Hospital Palembang in 2019–2020.Methods: This study is descriptive observational study conducted in October–November 2021. After having ethical approval from the Institutional Review Committee, research data were obtained from the medical records of young female patients diagnosed with breast cancer from January 1, 2019 to December 31, 2020. Samples were collected by using total sampling with the patient’s young age limit of fewer than 40 years.Results: The incidence of breast cancer was 20.9% (169 patients). The number of samples in this study was 120. Sociodemographic characteristics include the age range of 35–39 years around 63.3% (76 people), the highest education level of senior high school around 35% (42 people), not working around 73.3% (88 people), and living in the Palembang City area around 47.5% (57 people). Clinicopathological characteristics include the stage at the first diagnosis of stage IIIB about 46.7% (56 people), luminal B clinical subtype about 60% (72 people), and most histopathological type of invasive carcinoma of no special type about 88.3% (106 people).Conclusions: The incidence of breast cancer in young women is less than in older women but has worse cancer characteristics